BRAND GENDER AS THE ANTECEDENT OF BRAND LOVE MEDIATED BY COSRX SKINCARE CONSUMER ENGAGEMENT - Sulistyo, Desy Ari; Kirana, Erghana Kanza; Hendrati, Ignatia Martha; Handayani, Wiwik (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The aims of this research are to examine the influence of brand gender, consumer engagement, and brand love, and examine mediating effect of consumer engagement on the relationship between brand gender and brand love. The sample was 150 respondents and selected using nonprobability sampling e and purposive sampling technique. Sample criteria are consumers who had or were using COSRX for 3 months, female and had Instagram account. The data were collected by questionnaire, distributed online, and analyzed using structural equation modeling (SEM) with partial least square (PLS) as the method. The results showed that brand gender had a positive and significant effect on consumer engagement and brand love. Consumer engagement had a positive and significant effect on brand love. The mediation effect of the study also found that consumer engagement moderated and positive significantly the relationship between brand gender and brand love. Keywords: Brand gender, consumer engagement, brand love, COSRX